The impact of Ukrainian immigration on inter-voivodship migration in Poland – an attempt to estimate the regional “displacement” effect using the input-output method - Jurand Skrzypek (Managerial Economics)
The aim of the article is to estimate the strength of the “displacement” effect of the residents of Polish voivodeships to other regions of the country and determine the regional differentiation caused by the mass inflow of immigrants from Ukraine to Poland in 2022. The study used a modified input-output method, which allows for capturing and balancing both internal and external migration. The first stage of the study consisted in constructing inter-voivodeship migration tables, taking into account the inflow of immigrants from Ukraine. In the second stage of the study, the “displacement” effect was measured using the input-output method, which showed its strong spatial differentiation – the strongest effect was observed in voivodeships with a relatively higher level of the unemployment rate and lower wages (i.e. Warmińsko-Mazurskie and Świętokrzyskie), while the weakest – in voivodeships with large urban centres and capacious labour markets (i.e. Mazowieckie, Małopolskie, Dolnośląskie). The study also revealed a paradox, namely that the eastern provinces closest to Ukraine (i.e. Podkarpackie, Lubelskie) showed a relatively weak capacity to absorb Ukrainian immigrants, whose admission could cause greater disruptions in the local labour markets in these regions than in more distant provinces. The construction of the migration input-output tables was mainly based on data from the Bank Danych Lokalnych Głównego Urzędu Statystycznego (Local Data Bank of Central Statistical Office of Poland) and the Office for Foreigners for the years 2022 and 2015.